Humedad relativa y temperatura interna en colmenas de madera y asbesto-cemento - Ramirez, W.=700 1 Pontigo, M.
(Es, En)
Ilus., 5 ref.
Keywords: COLMENA; MADERA; CEMENTO; HUMEDAD RELATIVA; TEMPERATURA; FACTORES AMBIENTALES; COSTA RICA; ASBESTO; AGRONOMIA COSTARRICENSE